Isomalt and maltitol-based zinc-ion battery electrolyte, preparation method and application thereof

CN121601811BActive Publication Date: 2026-09-25HUBEI ENG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511532558.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-09-25
Estimated Expiration
2045-10-24

AI Technical Summary

Technical Problem

然而,传统水系电解液存在难以回避的问题:水分子间通过氢键形成的连续网络结构,会促使质子以Grotthuss机制快速传输

Benefits of technology

[0016](1)与异麦芽糖醇或麦芽糖醇相比,本发明以异麦芽糖醇和麦芽糖醇搭配作为水系锌离子电池的电解液添加剂,利用异麦芽糖醇和麦芽糖醇之间异构体偶极矩的差异,在电极/电解液界面创造一个梯度变化的偶极矩场。这个场能够引导锌离子进行更平缓、更均匀的横向迁移,从而极致地平滑锌离子浓度场,消除局部热点,从而达到抑制锌枝晶生成的效果,显著增强了水系锌离子电池的电化学稳定性能,提高电池的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121601811B_ABST
    Figure CN121601811B_ABST
Patent Text Reader

Abstract

The application discloses a zinc ion battery electrolyte based on isomaltitol and maltitol, a preparation method and application thereof, and belongs to the technical field of battery materials. The zinc ion battery electrolyte comprises a zinc salt, water and an additive, and the additive is composed of isomaltitol and maltitol. The application uses isomaltitol and maltitol as electrolyte additives of the aqueous zinc ion battery, utilizes the difference between isomaltitol and maltitol in isomer dipole moment, and creates a gradient change dipole moment field at the electrode / electrolyte interface. The field can guide the zinc ion to perform more gentle and uniform horizontal migration, thereby extremely smoothing the zinc ion concentration field, eliminating local hot spots, achieving the effect of inhibiting the generation of zinc dendrites, significantly enhancing the electrochemical stability of the aqueous zinc ion battery, and improving the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, specifically to a zinc-ion battery electrolyte based on isomaltitol and maltitol, its preparation method, and its application. Background Technology

[0002] Aqueous zinc-ion batteries (AZIBs) have shown significant application potential in large-scale energy storage due to their advantages such as high safety, low cost, and high theoretical capacity of zinc anodes (820 mAh / g), becoming a research hotspot in recent years. As the core carrier of ion transport and energy conversion in the battery, the performance of the electrolyte directly determines key indicators such as cycle stability and rate performance. Therefore, optimizing the electrolyte system is one of the core directions for improving the performance of AZIBs. However, traditional aqueous electrolytes have an unavoidable problem: the continuous network structure formed by hydrogen bonds between water molecules promotes the rapid transport of protons via the Grotthuss mechanism. On the negative electrode side, this structure leads to the enrichment of water molecules and the lack of Zn in the interfacial region. 2+ This can easily trigger the hydrogen evolution reaction (HER) and zinc dendrite growth, leading to negative electrode corrosion and short circuit risks; on the positive electrode side, Zn 2+ H + Co-intercalation with water molecules can exacerbate the volume expansion of materials and even lead to structural collapse, severely limiting the reversibility and lifespan of batteries.

[0003] To address these issues, researchers have attempted to introduce organic additives containing polar functional groups to suppress proton transport and reduce side reactions by disrupting the hydrogen bond network between water molecules. However, these additives often require large quantities to maintain their interaction with water; excessive addition leads to increased electrolyte viscosity and decreased dielectric constant, which in turn reduces ionic conductivity and reaction kinetics, creating a new performance bottleneck. Polyols (polyhydroxy organic molecules) possess both hydrogen bond donor and acceptor properties, making them highly promising electrolyte additives. The multiple hydroxyl groups in their molecules can form coordination interactions with water molecules, disrupting the existing hydrogen bond network, reducing water molecule activity, and decreasing its contact with the negative electrode, thereby inhibiting the hydrogen evolution reaction. Simultaneously, polyols can participate in the Zn... 2+ The formation of solvation structures optimizes the ion transport environment and promotes Zn 2+Uniform deposition inhibits dendrite growth. Furthermore, polyols have high solubility in water, allowing them to function effectively at lower addition levels, thus mitigating the problem of drastic viscosity increases in the electrolyte. For example, Chinese patent CN117080584B discloses an aqueous zinc-ion electrolyte additive containing maltitol and its application. This invention uses maltitol as an electrolyte additive. During zinc deposition, maltitol molecules preferentially adhere to the zinc metal anode surface through chemical adsorption, reducing direct contact between free water and the zinc metal surface. This reduces the hydrogen evolution reaction between free water and the zinc metal surface, inhibiting the formation of the byproduct sulfate. Additionally, zinc-ion batteries containing maltitol can generate a larger nucleation overpotential. This larger overpotential promotes the formation of a finer-grained zinc deposition layer, while also increasing the number of nucleation sites and decreasing the nucleation rate, thereby inhibiting zinc dendrite growth. However, using maltitol alone as an electrolyte additive has limited guiding effect on zinc ion flow to the electrode surface due to its weak and uneven adsorption capacity. Zinc ions still tend to preferentially deposit at the most energy-efficient locations (such as tips), thus exacerbating dendrite formation. Therefore, current zinc-ion batteries still suffer from side reactions such as zinc dendrite growth and hydrogen evolution, affecting their cycle stability and battery life. Designing a reasonable electrolyte additive formulation to achieve controllable zinc ion deposition / dissolution and suppress zinc dendrite growth remains a challenge for current research on aqueous zinc-ion batteries. Summary of the Invention

[0004] To address the shortcomings of existing technologies, one objective of this invention is to provide a zinc-ion battery electrolyte based on isomaltitol and maltitol. This invention introduces biomass-derived isomaltitol and maltitol as electrolyte additives for aqueous zinc-ion batteries. By utilizing the directional adsorption of the polyhydroxy groups of isomaltitol and maltitol on the zinc anode surface, a homogenized ion migration interface is constructed, thereby regulating zinc deposition behavior and inhibiting zinc dendrite formation, significantly improving the electrochemical stability of aqueous zinc-ion batteries.

[0005] The objective of this invention is achieved through the following technical solutions.

[0006] A zinc-ion battery electrolyte based on isomaltitol and maltitol, the zinc-ion battery electrolyte comprising zinc salt, water and additives, the additives being composed of isomaltitol and maltitol.

[0007] This invention uses isomaltitol and maltitol as electrolyte additives for aqueous zinc-ion batteries. By utilizing the directional adsorption of the polyhydroxy groups of isomaltitol and maltitol on the zinc anode surface, a homogenized ion migration interface is constructed, thereby regulating zinc deposition behavior. Simultaneously, the hydrogen bond network formed by the hydroxyl groups and free water reduces the activity of free water, minimizing side reactions such as hydrogen evolution and zinc corrosion. More importantly, this invention utilizes the difference in dipole moments between the isomers of isomaltitol and maltitol to create a gradient-changing dipole moment field at the electrode / electrolyte interface. This field guides zinc ions to migrate more smoothly and uniformly laterally, thereby extremely smoothing the zinc ion concentration field, eliminating local hot spots, and suppressing zinc dendrite formation. This significantly enhances the electrochemical stability of aqueous zinc-ion batteries and improves their cycle life.

[0008] Preferably, the concentration of zinc salt in the electrolyte is 1~3 mol / L.

[0009] Preferably, the concentration of the additive in the electrolyte is 0.01wt% to 0.05wt%.

[0010] Preferably, the mass ratio of isomaltitol to maltitol is (1~2):1.

[0011] Preferably, the zinc salt includes at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc nitrate, zinc chloride, and zinc acetate.

[0012] Another object of the present invention is to provide a method for preparing the zinc-ion battery electrolyte based on isomaltitol and maltitol, comprising the following steps: dissolving the zinc salt in water, then adding the isomaltitol and maltitol, and stirring evenly at 20~60°C to obtain the zinc-ion battery electrolyte.

[0013] Another object of the present invention is to provide the application of the zinc-ion battery electrolyte based on isomaltitol and maltitol in aqueous zinc-ion batteries.

[0014] The present invention also provides an aqueous zinc-ion battery, which is composed of a positive electrode, a negative electrode, a separator and the above-mentioned zinc-ion battery electrolyte.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0016] (1) Compared with isomaltitol or maltitol, this invention uses isomaltitol and maltitol in combination as electrolyte additives for aqueous zinc-ion batteries. Utilizing the difference in dipole moments between the isomers of isomaltitol and maltitol, a gradient-changing dipole moment field is created at the electrode / electrolyte interface. This field guides zinc ions to migrate more smoothly and uniformly laterally, thereby extremely smoothing the zinc ion concentration field, eliminating local hot spots, and thus suppressing zinc dendrite formation. This significantly enhances the electrochemical stability of aqueous zinc-ion batteries and improves their cycle life.

[0017] (2) Compared with isomaltitol or maltitol, the combination of isomaltitol and maltitol in this invention as electrolyte additives for aqueous zinc-ion batteries can significantly improve the initial specific capacity and cycle stability of the battery, and the battery exhibits superior electrochemical stability.

[0018] (3) The electrolyte of the present invention is green, environmentally friendly and low in cost. It can be obtained by a simple dissolution method and then applied to aqueous zinc-ion battery electrolytes. Attached Figure Description

[0019] Figure 1 Comparative images of ISO@Mal-E from Example 1, ISO-E from Comparative Example 1, Mal-E from Comparative Example 2, and ZnSO4 solution.

[0020] Figure 2 Fourier transform infrared spectra of ISO@Mal-E in Example 1, ISO-E in Comparative Example 1, Mal-E in Comparative Example 2, and ZnSO4 solutions.

[0021] Figure 3 The long-cycle performance diagram and charge-discharge curve of Zn / / Zn symmetric cell are shown.

[0022] Figure 4 Coulomb efficiency plot and charge / discharge curve plot for Zn / / Cu half-cell;

[0023] Figure 5 For Zn / / (NH4) x Cyclic performance graph and charge / discharge curve of VO3 full battery;

[0024] Figure 6 SEM image of the negative electrode after cycling in a Zn / / Zn symmetrical battery;

[0025] Figure 7 For Zn / / (NH4) x CV cycle diagram of a full VO3 cell;

[0026] Figure 8 A voltage test diagram of three full batteries connected in series and an image of an LED light being lit.

[0027] Figure 9 The molecular structural formulas for ISO and Mal are given. Detailed Implementation

[0028] The applicant will now provide a detailed description of the method of the present invention with reference to specific embodiments, in order to enable those skilled in the art to clearly understand the present invention. However, the following embodiments should not be construed in any way as limiting the scope of protection claimed in the present invention.

[0029] The zinc-ion battery electrolyte of the present invention, based on isomaltitol and maltitol, comprises zinc salt, water, and additives, wherein the additives are composed of isomaltitol and maltitol.

[0030] In some embodiments, the concentration of zinc salt in the electrolyte is 1 mol / L; in other embodiments, the concentration of zinc salt in the electrolyte is 3 mol / L; and in some preferred embodiments, the concentration of zinc salt in the electrolyte is 2 mol / L.

[0031] In some embodiments, the concentration of the additive in the electrolyte is 0.01 wt%; in other embodiments, the concentration of the additive in the electrolyte is 0.05 wt%; and in some preferred embodiments, the concentration of the additive in the electrolyte is 0.03 wt%.

[0032] In some embodiments, the mass ratio of isomaltitol to maltitol is 1:1; in other embodiments, the mass ratio of isomaltitol to maltitol is 2:1.

[0033] In some embodiments, the zinc salt may be selected from at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc nitrate, zinc chloride, and zinc acetate.

[0034] Example 1

[0035] This embodiment provides a method for preparing a zinc-ion battery electrolyte based on isomaltitol and maltitol, including the following steps:

[0036] An electrolyte additive is obtained by mixing isomaltitol (ISO) and maltitol (Mal) in a mass ratio of 1:1.

[0037] Weigh 17.24 g of ZnSO4•7H2O, add it to 30 mL of water to dissolve it, and obtain a 2 mol / L ZnSO4 solution. Then add electrolyte additive at a mass of 0.03% of the total mass of the solution. Stir with a glass rod at 25 °C until the mixture is homogeneous to obtain the electrolyte, denoted as ISO@Mal-E.

[0038] Comparative Example 1

[0039] This comparative example provides a method for preparing a zinc-ion battery electrolyte based on isomaltitol, comprising the following steps: weighing 17.24 g of ZnSO4•7H2O, adding it to 30 mL of water to dissolve it, obtaining a 2 mol / L ZnSO4 solution, then adding ISO at a mass of 0.03% of the total mass of the solution, stirring with a glass rod at 25 °C until the mixture is homogeneous, and obtaining the electrolyte, denoted as ISO-E.

[0040] Comparative Example 2

[0041] This comparative example provides a method for preparing a zinc-ion battery electrolyte based on maltitol, comprising the following steps: weighing 17.24 g of ZnSO4•7H2O, adding it to 30 mL of water to dissolve it, obtaining a 2 mol / L ZnSO4 solution, then adding Mal at a mass of 0.03% of the total mass of the solution, stirring with a glass rod at 25 °C until the mixture is homogeneous, and obtaining the electrolyte, denoted as Mal-E.

[0042] Figure 1 The figures show a comparison of the ISO@Mal-E solution of Example 1, ISO-E solution of Comparative Example 1, Mal-E solution of Comparative Example 2, and ZnSO4 solution. As can be seen from the figures, all four solutions are transparent and colorless.

[0043] Fourier transform infrared spectroscopy was performed on the ISO@Mal-E solution of Example 1, the ISO-E solution of Comparative Example 1, the Mal-E solution of Comparative Example 2, and the ZnSO4 solution. The results are as follows: Figure 2 As shown in the figure, compared with ZnSO4 solution, ISO-E, or Mal-E, the antisymmetric stretching vibration (v) of OH in the ISO@Mal-E curve is significantly higher. a (OH)) and symmetric stretching vibration (v s The peak position and shape of (OH) have changed, and the sulfate ion (v(SO4)) has changed. 2- The absorption peaks also changed, indicating that ISO and Mal interacted with water molecules, sulfate ions, etc. in the electrolyte, which changed the vibrational environment of these groups and thus affected the solvation structure of zinc ions. This had a positive effect on the migration and deposition of zinc ions during the battery charging and discharging process.

[0044] Example 2

[0045] The preparation method of the zinc-ion battery electrolyte based on isomaltitol and maltitol in this embodiment is basically the same as that in Example 1, except that ISO and Maltitol are mixed at a mass ratio of 2:1 to obtain the electrolyte additive.

[0046] Example 3

[0047] The preparation method of the zinc-ion battery electrolyte based on isomaltitol and maltitol in this embodiment is basically the same as that in Example 1, except that the electrolyte additive accounts for 0.01% of the total mass of the solution.

[0048] Example 4

[0049] The preparation method of the zinc-ion battery electrolyte based on isomaltitol and maltitol in this embodiment is basically the same as that in Example 1, except that the electrolyte additive accounts for 0.05% of the total mass of the solution.

[0050] Application examples

[0051] (1) Preparation of materials

[0052] Zn / / (NH4) x Preparation of the positive electrode sheet for VO3 full battery: Ammonium vanadate, acetylene black, and polyvinylidene fluoride, the positive electrode active material, are mixed in a mass ratio of 7:2:1. N-methylpyrrolidone is added to form a uniform slurry, which is then coated onto a carbon paper substrate and dried to obtain the positive electrode sheet. The dried positive electrode sheet is then punched to a diameter of 12 mm to obtain the positive electrode sheet.

[0053] Zinc and copper sheets with a diameter of 12 mm, zinc sheets with a diameter of 15 mm, and diaphragms with a diameter of 16 mm are produced using a stamping machine.

[0054] (2) Assemble the battery

[0055] Using ISO@Mal-E from Example 1, ISO-E from Comparative Example 1, Mal-E from Comparative Example 2, and ZnSO4 solution as electrolytes, the negative electrode shell, zinc sheet, separator, electrolyte, zinc sheet, gasket, spring, and positive electrode shell were assembled sequentially. The battery was then placed in the device and pressed tightly to obtain Zn / / Zn symmetric batteries using ISO@Mal-E, ISO-E, Mal-E, and ZnSO4 solutions as electrolytes, respectively.

[0056] Following the above method, using a copper sheet with a diameter of 12 mm as the positive electrode and a zinc sheet with a diameter of 12 mm as the negative electrode, Zn / / Cu half-cells were obtained with ISO@Mal-E, ISO-E, Mal-E and ZnSO4 solutions as electrolytes, respectively.

[0057] Then, using the 12 mm diameter positive electrode sheet prepared in step (1) as the positive electrode and the 15 mm diameter zinc sheet as the negative electrode, Zn / / (NH4) was obtained with ISO@Mal-E, ISO-E, Mal-E and ZnSO4 solutions as electrolytes, respectively. x VO3 full battery.

[0058] (3) Zn / / Zn symmetric cell test

[0059] The Zn / / Zn symmetric cell assembled in step (2) was tested on a blue electric field testing system at 5 mA / cm². 2 Current density, 1 mAh / cm 2 Under specific capacity conditions, constant current charge-discharge tests were conducted. The battery cycle stability was tested by performing the following steps in sequence: rest, constant current charging, rest, and constant current discharging. The rest period was 30 seconds for each step, and the constant current charge-discharge time was 0.2 hours.

[0060] The long-cycle performance diagram and charge-discharge curve of Zn / / Zn symmetric cells are as follows: Figure 3 As shown in Figure a, which is the long-cycle performance diagram of the four sets of symmetric cells, it can be seen that the Zn / / Zn symmetric cell with ZnSO4 solution as electrolyte short-circuited after 80h. The Zn / / Zn symmetric cells with ISO-E and Mal-E as electrolytes also short-circuited after 150h and 370h, respectively. However, the Zn / / Zn symmetric cell with ISO@Mal-E as electrolyte has stable cycling performance for more than 750h. Figures b, c, d, and e show the charge-discharge curves of Zn / / Zn symmetric batteries using ISO@Mal-E, Mal-E, ISO-E, and ZnSO4 solutions as electrolytes at 50, 100, 200, and 250 cycles, respectively. The figures show that the polarization voltage of the Zn / / Zn symmetric battery using ZnSO4 solution as electrolyte is 106 mV, while the polarization voltages of the Zn / / Zn symmetric batteries using ISO@Mal-E, Mal-E, and ISO-E electrolytes are 84 mV, 90 mV, and 86 mV, respectively. The polarization voltages of the three groups of batteries are similar, but all are lower than the polarization voltage of ZnSO4. However, compared with ISO or Mal as a single additive, using ISO and Mal as a composite additive significantly improves the cycle stability of the aqueous zinc-ion battery.

[0061] (4) Zn / / Cu half-cell test

[0062] The Zn / / Cu half-cell assembled in step (2) was tested on a blue electric field testing system at 5 mA / cm². 2 Constant current charge-discharge tests were conducted at current density, following the sequence of rest, constant current discharge, rest, and constant current charge. The rest period was 30 seconds for each test, and the constant current charge-discharge time was 12 minutes. The coulombic efficiency of the battery was then tested.

[0063] The coulombic efficiency diagram and charge / discharge curve of the Zn / / Cu half-cell are shown below. Figure 4As shown in Figure a, the coulombic efficiency of the four groups of half-cells is as follows: Figure a shows the cycle life of the half-cells using ZnSO4 solution, Mal-E, and ISO-E as electrolytes (50, 135, and 165 cycles respectively). The half-cell using ISO@Mal-E as electrolyte achieves over 400 stable cycles with a coulombic efficiency consistently above 99.9%, indicating a longer cycle life. This demonstrates that using ISO@Mal-E as electrolyte significantly improves the cycle life compared to ZnSO4 solution, Mal-E, or ISO-E. Figures b, c, d, and e show the charge-discharge curves of the Zn / / Cu half-cells using ISO@Mal-E, Mal-E, ISO-E, and ZnSO4 solution as electrolytes at cycles 3, 10, 30, and 50, respectively. The figures show that the polarization voltages of the four Zn / / Cu half-cells are not significantly different.

[0064] (5) Zn / / (NH4) x VO3 full battery test

[0065] The Zn / / (NH4) assembled in step (2) x The VO3 full battery was tested on the Blue Electric Test System. Constant current charge and discharge was performed under the conditions of 5A / g current density and 0.4~1.8V charge and discharge range to test the cycle stability of the battery.

[0066] Zn / / (NH4) x The cycle performance diagram and charge / discharge curve of the VO3 full battery are as follows: Figure 5 As shown in the figures, Figure a presents the cycle performance of four groups of full cells. It can be seen from the figure that, compared with ZnSO4 solution, Mal-E, or ISO-E, the full cell using ISO@Mal-E as the electrolyte has a significantly increased initial specific capacity, reaching 350 mAh / g, and exhibits better cycle stability. Figures b, c, d, and e show the Zn / / (NH4) cycles using ISO@Mal-E, Mal-E, ISO-E, and ZnSO4 solution as electrolytes, respectively. x The charge-discharge curves of the VO3 full cell at 50, 100, 200, and 250 cycles show that the charge-discharge plateau is more stable in the full cell system using ISO@Mal-E as the electrolyte at different cycle counts, and the plateau decays slowly with increasing cycle count. In contrast, the charge-discharge plateau decays rapidly in battery systems using only electrolytes with Mal or ISO as additives, and in battery systems using ZnSO4 as the electrolyte.

[0067] In an electrochemical workstation, ISO@Mal-E and ISO electrolytes were used at a current density of 5 mA / cm². 2 The Zn / / Zn symmetric cell was cycled once, and then the negative electrode was subjected to SEM testing, as shown below. Figure 6 As shown in the figure, Figure a is a SEM image of the negative electrode with ISO@Mal-E as the electrolyte; Figure b is a SEM image of the negative electrode with ISO-E as the electrolyte. It can be seen that compared with ISO-E alone, zinc ions are deposited evenly on the zinc surface with ISO@Mal-E as the electrolyte, which indicates that the addition of this additive regulates the deposition of zinc ions.

[0068] Furthermore, Zn / / (NH4) using ISO@Mal-E as the electrolyte... x VO3 full cells were subjected to CV testing under the following conditions: CHI660E electrochemical workstation, voltage range of 0.4~1.4V and scan rate of 1~10 mV / s.

[0069] Zn / / (NH4) x The CV cycle diagram of a full VO3 cell is shown below. Figure 7 As shown in the figure, the oxidation / reduction peaks stabilize as the scan rate increases, indicating faster charge transport and lower internal resistance. Furthermore, the oxidation and reduction peaks exhibit high symmetry, suggesting that the reaction has good reversibility.

[0070] Furthermore, three assembled full cells using ISO@Mal-E as the electrolyte were connected in series. After charging, their voltage was measured, as well as whether they could light up an LED. The voltage test graph of the three full cells connected in series and the image of the LED lit up are shown below. Figure 8 As shown in the figure, the results indicate that charging and discharging can proceed normally, and the LED lights can be lit normally.

[0071] In summary, the results above all indicate that using ISO@Mal-E as the electrolyte significantly improves the cycle stability of the battery compared with using ZnSO4 solution, Mal-E, and ISO-E as the electrolyte.

[0072] Figure 9 Figure 1 shows the molecular structure of ISO and Mal, where (a) is the molecular structure of ISO and (b) is the molecular structure of Mal.

[0073] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A zinc-ion battery electrolyte based on isomaltitol and maltitol, characterized in that, The zinc-ion battery electrolyte includes zinc salt, water, and additives. The concentration of the additives in the electrolyte is 0.01wt% to 0.05wt%, and the additives are composed of isomaltitol and maltitol in a mass ratio of (1 to 2):

1.

2. The zinc-ion battery electrolyte based on isomaltitol and maltitol according to claim 1, characterized in that, The concentration of zinc salt in the electrolyte is 1~3 mol / L.

3. The zinc-ion battery electrolyte based on isomaltitol and maltitol according to claim 1, characterized in that, The zinc salt includes at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc nitrate, zinc chloride, and zinc acetate.

4. The method for preparing the zinc-ion battery electrolyte based on isomaltitol and maltitol according to any one of claims 1 to 3, characterized in that, The process includes the following steps: dissolving the zinc salt in water, then adding isomaltitol and maltitol, and stirring evenly at 20-60°C to obtain the zinc-ion battery electrolyte.

5. The application of the zinc-ion battery electrolyte based on isomaltitol and maltitol as described in any one of claims 1 to 3 in an aqueous zinc-ion battery.

6. An aqueous zinc-ion battery, characterized in that, The aqueous zinc-ion battery is composed of a positive electrode, a negative electrode, a separator, and the zinc-ion battery electrolyte as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Aqueous zinc ion electrolyte additive containing maltitol and application thereof

    CN117080584B

  • Low-sugar, high-fiber chewing candy

    CN119095494A

  • Extremely low temperature resistant gel electrolyte and preparation method and application thereof

    CN119542523A